The Justinian system: one of the oldest flood control facilities in the world - Yazgan, Mustafa S.; Yenigün, Kasım; Kürkçüoğlu, A. Cihat (IWA Publishing, 2013)
In ancient times, the city of Urfa suffered serious flood disasters due to the Karakoyun river which surrounded the city on the north and west sides. In order to prevent the recurrence of such disasters, in 525, the Byzantine Emperor Justinian had built a huge wall of stone (Justinian wall) to the northwest of the city that conducted the river to the north and east walls of the city. He also constructed an artificial channel and three bridges which are known as the Justinian system. This system has been used by the many civilizations that have occupied the city, since the 6th century. Each civilization added some new water structures to the system and carried out some renovations to it. The system, being still in use, defended the city against moderate size floods and survived for 1,500 years. In this paper, the Justinian system is evaluated from the hydraulic point of view together with its ongoing functionality. It is interesting that although the cultural structures of the civilizations settled in the city do not have the same characteristics, the water structures have similar features in terms of hydraulic and architectural perspectives.